If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + -3z = 61 Solving 7y + -3z = 61 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3z' to each side of the equation. 7y + -3z + 3z = 61 + 3z Combine like terms: -3z + 3z = 0 7y + 0 = 61 + 3z 7y = 61 + 3z Divide each side by '7'. y = 8.714285714 + 0.4285714286z Simplifying y = 8.714285714 + 0.4285714286z
| 2x^3+18x^2+36=0 | | -9=4+h | | 2y-5z=5 | | 2m=56 | | 2X+11+4X-3=180 | | s=180(4y-2) | | -2x-4(-3x-14)=-54 | | X+4z=13 | | log(3x)=2.1 | | 56x+56=42x+42 | | 2=18-4 | | 2n^2+7=-4n+5 | | y=x-19/-6 | | 4logx=-12 | | 76+28x=18x-4 | | 2=-x+3x^2 | | 2pir=88 | | X=1/2(105) | | 10y-4=y+6 | | (2n+12)= | | 4x^2-8+25=81 | | 6(2x+y)+2y-12x= | | -107=7x+6(3x+3) | | 2d^2-32=-32 | | 8.3=3-2.5c | | 17p=3 | | x^2-13x+42.25= | | 312.8z+(kz^2)=37223 | | X=1/2(20) | | 4x+8=7-2x | | 12x=-x+121 | | -48=4d |